Firm Performance Before and After Horizontal Merger and Acquisition Effectiveness and Efficiency Performance on Hotel Industry in Indonesia - Sopyan, Adi (Sekolah Tinggi Manajemen Pariwisata dan Logistik Lentera Mondial, 2025)
The literature frequently highlights synergy as the main goal behind M&As, research often shows a lack of success, casting doubt on the potential to achieve these synergies. One area that has not been extensively explored is the overall impact of M&As. This study seeks to examine how marketing effectiveness and efficiency influence firm performance, and how these effects vary before and after a horizontal M&A. We developed hypotheses and tested them Hotel Industry in Indonesia. Our results indicate that marketing effectiveness positively impacts firm performance both before and after the M&A, with a stronger effect observed after the M&A. Conversely, efficiency does not affect firm performance before the M&A but shows a positive impact afterward.